Acute effects of repeated isoinertial lunges on jump and sprint parameters - Mehmet Kale; Emre Celik; Ezgi Ayaz; Esen Kızıldağ Kale (Physical Education of Students)
Background and Study Aim. Understanding the relationship between repeated isoinertial lunges and jump and sprint parameters is an important factor in achieving success in sports requiring explosive strength and speed. The aim of this study was to examine the acute effects of repeated isoinertial lunges on jump and sprint parameters.